A method for evaluating the aging degree of silicone rubber
By spraying photoluminescent materials on the silicone rubber composition and using laser excitation to measure the light intensity attenuation curve, the problem of difficulty in evaluating the aging degree of silicone rubber in the prior art is solved, and a convenient, lossless and quantitative assessment of aging degree is achieved .
Patent Information
- Application Number
- CN202210960041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-08-11
AI Technical Summary
The existing technology is difficult to evaluate the aging degree of silicone rubber online and conveniently, resulting in the safe operation of the power grid facing major hidden dangers.
By spraying a silicone rubber composition containing a photoluminescent material onto the intended coating, and after curing, the photoluminescent material is excited using a laser emitter, the variation of emitted light intensity over time is measured, and the light intensity attenuation curve is analyzed to evaluate silicon Rubber aging degree.
It realizes that the degree of aging of silicone rubber can be evaluated online and conveniently without power outage, the test is lossless, can be performed multiple times, and the degree of aging of silicone rubber can be described in a quantitative manner.
Smart Images

Figure CN115452780B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for evaluating the aging degree of rubber, and in particular to a method for evaluating the aging degree of silicone rubber. Background Art
[0002] Room temperature vulcanized silicone rubber anti-pollution flashover coating and high temperature vulcanized silicone rubber shed have excellent electrical insulation and hydrophobicity, which can effectively prevent the occurrence of pollution flashover accidents. As an effective means of preventing pollution flashover, room temperature vulcanized anti-pollution flashover coating and high temperature vulcanized silicone rubber shed have been widely used in the power industry. However, after a certain period of operation, under the influence of continuous fog, rain, snow and other environmental factors, the silicone rubber will age, the shed surface will be moistened, the surface resistivity of the insulator will decrease, the leakage current will increase, resulting in uneven voltage distribution of the insulator string, partial discharge, and the arc generated will further damage the coating surface, becoming a major hidden danger to the safe operation of the power grid. For the problem of aging of room temperature vulcanized silicone rubber anti-pollution flashover coating and high temperature vulcanized silicone rubber shed, at this stage, workers are required to conduct manual inspection and regular re-spraying. The maintenance, maintenance and renewal of such a large number of anti-pollution flashover coatings require a lot of manpower, material and financial resources.
[0003] Therefore, there is a need for a method for evaluating the aging degree of silicone rubber that does not require power outage and is online and convenient. Summary of the invention
[0004] Purpose of the invention: The present invention aims to provide a method for evaluating the aging degree of silicone rubber which can be directly evaluated online.
[0005] Technical solution: The method for evaluating the aging degree of silicone rubber according to the present invention comprises the following steps:
[0006] (1) spraying / coating a silicone rubber composition containing a photoluminescent material on an object to be coated;
[0007] (2) after the silicone rubber composition is cured, using a laser emitter to emit excitation light to the silicone rubber composition;
[0008] (3) using a light intensity tester to measure the emission intensity of the silicone rubber composition excited in step (2), and recording the change of the light intensity of the silicone rubber composition over time as data set 1;
[0009] (4) After the coating material is aged, a laser emitter is used to emit excitation light to the silicone rubber composition at the location where the silicone rubber aging degree is to be detected, thereby exciting the silicone rubber composition;
[0010] (5) using a light intensity tester to measure the emission intensity of the silicone rubber composition excited in step (4), and recording the change of the light intensity of the silicone rubber composition over time as data set 2;
[0011] (6) analyzing the light intensity versus time curve (light intensity decay curve) recorded in step (5) to evaluate the aging degree of the silicone rubber composition;
[0012] The measurement of the change in light intensity of the silicone rubber composition over time in step (3) and step (5) should be carried out at the same time as the excitation of the silicone rubber composition in step (2) and step (4) is completed respectively;
[0013] (7) Data analysis:
[0014] (71) The following formula is used to fit the data of data set 1, and I 0 and τ:
[0015]
[0016] Where, I is the luminescence intensity after the excitation stops at t; I 0 is the luminous intensity when the excitation just stops; τ is the average lifetime of the electron in the excited state, which is also called the decay constant; K is a constant, which can be described as K = I 0 *b (A.Hayer et al., J.Phys.Chem.A 2002,106,11045-11053), where b is called the bimolecular annihilation constant, which describes the radiation transition of excited state fluorescent molecules and can be described as b = (k p +k d ), k p , k d They are the phosphorescence emission rate and the intersystem crossing rate, respectively (G. Croizat et al., Journal of Photochemistry & Photobiology, B: Biology 2020, 209, 111887).
[0017] (72) The data of data set 2 are fitted using τ obtained in step (71) and the following formula to obtain I 1 :
[0018]
[0019] (73) The degree of aging of silicone rubber is defined as:
[0020]
[0021] The light intensity versus time curve (light intensity decay curve) can be analyzed using commercial software (program), customized software (program) or homemade software (program).
[0022] The measurement of the change in light intensity of the silicone rubber composition over time in step (3) and step (5) should be carried out at the same time when the excitation of the silicone rubber composition in step (2) and step (4) is completed, respectively.
[0023] The measurement time of the emission intensity of the silicone rubber composition excited in step (3) and step (5) can be 1s-400s, preferably 20s-200s, more preferably 30s-100s.
[0024] The amount of collected data on the emission intensity of the silicone rubber composition excited in step (3) and step (5) may be 10-100, preferably 20-50, and more preferably 30-40.
[0025] Here, steps (4) to (6) may be repeated multiple times after the coating has been used for different periods of time (ie, after different aging times).
[0026] There is no special limitation on the laser emitter, as long as the laser emitter can provide suitable excitation light to excite the photoluminescent material to be excited in the present invention. The laser emitter can be a commercially available product or a customized product. The laser emitter can be a MINI free space laser, an M-BIOS free space laser, a single / multi-mode fiber laser, a multi-wavelength laser, an industrial laser, etc.
[0027] The wavelength of the excitation light provided by the laser emitter depends on the photoluminescent material to be excited. The wavelength range of the excitation light can be 200nm-1500nm, for example, 375nm, 405nm, 415nm, 420nm, 450nm, 488nm, 505nm, 515nm, 520nm, 525nm, 529nm, 532nm, 550nm, 561nm, 633nm, 638nm, 648nm, 660nm, 670nm, 685nm, 690nm, 730nm, 785nm, 808nm, 830nm, 850nm, 980nm and 1064nm, etc.; preferably, the wavelength range of the excitation light can be 250nm-850nm; more preferably, the wavelength range of the excitation light can be 300nm-400nm.
[0028] The power of the laser emitter needs to meet the following conditions: the intensity of the excitation light provided by the laser emitter can excite the photoluminescent material to be excited. The power of the laser emitter is determined according to the safe operation distance.
[0029] The irradiation time (excitation time) of the laser emitter to irradiate the in-service silicone rubber composition to be inspected may be 10s-20min, preferably 15s-10min, and more preferably 30s-3min.
[0030] There is no special limitation on the light intensity tester, as long as it can test the intensity of the excitation light emitted by the photoluminescent material to be excited after being excited. The light intensity tester can be a commercial product or a customized product.
[0031] The silicone rubber composition contains the following raw materials in percentage by mass:
[0032]
[0033] The wavelength of the excitation light provided by the laser emitter in step (2) depends on the photoluminescent material to be excited, and the wavelength range of the excitation light is 200nm-1500nm.
[0034] The mass fraction of the photoluminescent material particles is preferably 0.1%-20%, more preferably 1%-10%.
[0035] The photoluminescent material is a material that emits light under light stimulation, and may be an organic photoluminescent material and / or an inorganic photoluminescent material and / or a photoluminescent material formed by hybridization, compositeness, or modification.
[0036] The photoluminescent material particles may be one or more photoluminescent materials.
[0037] The photoluminescent material may be selected from one or more of aluminates, silicates, phosphates, borates, sulfides, sulfur oxides, nitrides, etc. For example, SrAl 2 O 4 :Eu 2+ ,Dy 3+ , CaAl 2 O 4 :Eu 2+ ,Dy 3+ , Sr 4 Al 14 O 25 :Eu 2 + ,Dy 3+ , Sr 2 MgSi 2 O 7 :Eu 2+ ,Dy 3+ , Ca 2 MgSi 2 O 7 :Eu 2+ ,Dy 3+ MgSiO 3 :Mn 2+ ,Eu 2+ ,Dy3+ 、Cd 2 Ge 7 O 16 :Mn 2+ MgSnO 4 :Mn 2+ , Sr 2 P 2 O 7 :Eu 2+ ,Y 3+ wait.
[0038] Wherein, the polymer base glue is polysiloxane, including at least one of hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane and methylvinyl polysiloxane. The viscosity of hydroxyl-terminated polydimethylsiloxane is 500-40000mPa.s, preferably 1000-30000mPa.s, more preferably 3000-20000mPa.s. The viscosity of vinyl-terminated polydimethylsiloxane is 300-100000mPa.s, preferably 800-20000mPa.s, further preferably 1000-15000mPa.s. The molecular weight of methylvinyl polysiloxane is 400,000-800,000, preferably 500,000-700,000, and the vinyl content is 0.1%-0.5%, preferably 0.12%-0.3%.
[0039] Wherein, the reinforcing filler is at least one of precipitated silica, fumed silica, and ultrafine calcium carbonate.
[0040] Among them, the electrical corrosion resistant filler is at least one of aluminum hydroxide, magnesium hydroxide, double metal hydroxide, silicon oxide, aluminum oxide, boron nitride, layered silicate, ammonium polyphosphate, and melamine cyanurate, preferably aluminum hydroxide, double metal hydroxide, ammonium polyphosphate, and melamine cyanurate, and more preferably aluminum hydroxide and double metal hydroxide.
[0041] Among them, the inorganic filler is one or more of pigment, titanium oxide, magnesium oxide, antimony oxide, iron oxide, copper oxide, zinc oxide, silicon carbide, silicon nitride, calcium carbonate, mica, talc, kaolin, glass powder, montmorillonite, wollastonite, barium sulfate, and calcium sulfate, preferably pigment, titanium oxide, antimony oxide, iron oxide, calcium carbonate, mica, kaolin, montmorillonite, and wollastonite, and more preferably pigment, titanium oxide, iron oxide, calcium carbonate, mica, and montmorillonite.
[0042] Among them, the silicone oil is one or more of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, cyanide silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl chlorophenyl silicone oil, methyl ethoxy silicone oil, methyl trifluoropropyl silicone oil, methyl vinyl silicone oil, methyl hydroxy silicone oil, ethyl hydrogen silicone oil, hydroxy hydrogen silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, polyether-modified silicone oil, and carboxyl-modified silicone oil, preferably methyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl vinyl silicone oil, methyl hydroxy silicone oil, ethyl hydrogen silicone oil, hydroxy hydrogen silicone oil, and amino-modified silicone oil, and more preferably methyl silicone oil, phenyl silicone oil, methyl phenyl silicone oil, methyl hydroxy silicone oil, and hydroxy hydrogen silicone oil.
[0043] Wherein, the silane coupling agent is one or more of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane, and hexamethyldisilazane, preferably γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, and hexamethyldisilazane, and more preferably γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, and hexamethyldisilazane.
[0044] Wherein, the crosslinking agent is at least one of methyltributylacetonato oxime silane, vinyltributylacetonato oxime silane, phenyltributylacetonato oxime silane, tetrabutylketone oxime silane, methyltriacetone oxime silane and vulcanizing agent di-25.
[0045] Wherein, the catalyst is dibutyltin diacetate, a delayed platinum complex, stannous octoate and / or a Custer catalyst.
[0046] In the process of preparing silicone rubber coating, solvent gasoline, trichloropropane, trichloroethane, composite solvent, etc. can be used as dissolving medium.
[0047] In the process of preparing silicone rubber coating, other functional fillers can also be added, for example, stabilizers (such as 1-ethynylcyclohexanol, 3,7,11-trimethyldodecene-3-ol, tetramethyltetravinylcyclotetrasiloxane), flame retardants (such as hydrotalcite, antimony trioxide, decabromodiphenylethane, platinum-containing flame retardants, rhodium-containing flame retardants).
[0048] Principle of the invention: Photoluminescent materials all have afterglow characteristics. Compared with light-storage materials, they only decay faster and have shorter afterglow. Most photoluminescent materials decay exponentially after the light excitation stops, and follow the following formula:
[0049]
[0050] Where, I is the luminescence intensity after the excitation stops at t; I 0 is the luminous intensity when the excitation just stops; τ is the average lifetime of the electron in the excited state, also called the decay constant; K is a constant.
[0051] After aging, the surface hydrophobicity of the room temperature vulcanized silicone rubber anti-fouling flashover coating and the high temperature vulcanized silicone rubber shed will decrease. As a result, moisture will enter the silicone rubber anti-fouling flashover coating and the high temperature vulcanized silicone rubber, rendering the photoluminescent material contained in the silicone rubber ineffective, thereby causing it to lose its photoluminescent function.
[0052] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) the degree of aging of silicone rubber can be evaluated in an online and convenient manner without power outage; (2) the test is a non-destructive test; (3) multiple evaluations can be performed; (4) the degree of aging of silicone rubber can be described quantitatively. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is a flow chart of the method of the present invention;
[0054] Figure 2 The scattered points in the middle are the data of the brightness change over time of the samples of Example 1 of the present invention after aging for different time periods, and the solid line is the curve fitted according to the formula;
[0055] Figure 3 The hydrophobicity test result of the sample of Example 1 of the present invention conducted according to DL / T 627-2018 “Room-temperature curing silicone rubber anti-pollution flashover coating for insulators” when the sample is not aged;
[0056] Figure 4 The hydrophobicity test result of the sample of Example 1 of the present invention after 5 aging cycles according to DL / T 627-2018 “Room-temperature curing silicone rubber anti-pollution flashover coating for insulators”;
[0057] Figure 5 The hydrophobicity test result of the sample of Example 1 of the present invention after 10 aging cycles according to DL / T 627-2018 “Room-temperature curing silicone rubber anti-pollution flashover coating for insulators”;
[0058] Figure 6The hydrophobicity test result of the sample of Example 1 of the present invention after 20 aging cycles according to DL / T 627-2018 “Room-temperature curing silicone rubber anti-pollution flashover coating for insulators”;
[0059] Figure 7 This is the result of the hydrophobicity test of the sample in Example 1 of the present invention after 30 aging cycles according to DL / T 627-2018 "Room-temperature curing silicone rubber anti-pollution flashover coating for insulators". DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0061] The flow chart of the evaluation method of the present invention is shown in Figure 1 .
[0062] Example 1
[0063] Room temperature vulcanized anti-fouling flashover silicone rubber composition sample preparation:
[0064] (1) 100 kg of hydroxyl-terminated polydimethylsiloxane with a viscosity of 5000 mPa.s, 0.5 kg of hydroxyl silicone oil, and 10 kg of hydrophobically modified nano-silica were placed in a vacuum kneader and kneaded at 120-140°C and -0.1 MPa. After stirring and kneading evenly, 2 kg of SrAl 2 O 4 :Eu 2+ ,Dy 3+ , 90kg aluminum hydroxide, 20kg silicon oxide, fully knead and evenly mix, and use a three-roll mill for 3 times to further disperse evenly until it becomes a particle-free viscous liquid;
[0065] (2) adding the uniformly kneaded rubber material into a planetary disperser, adding 200 kg of solvent gasoline, 2 kg of vinyl trimethoxysilane, 2 kg of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 5 kg of methyl tributylidene oxime silane, and 0.3 kg of dibutyltin diacetate, and uniformly dispersing at a stirring speed of 2000 rpm, vacuum degassing, and discharging and canning to obtain a uniform mixture;
[0066] (3) The mixture obtained in step (2) is coated on a glass sheet to prepare a sample of 1.5 cm×1.5 cm×0.3 mm for later use.
[0067] Aging process:
[0068] The obtained samples were stored in a dry environment at 180°C for 24 hours, and then placed in a hot and humid environment at 90°C and 100% RH for 24 hours to accelerate the aging of the samples. The above process was considered as one cycle, and the cycle was repeated 5 times, 10 times, 15 times, 20 times, and 30 times.
[0069] Performance Test:
[0070] (1) Brightness test: In a simulated sunlight with a brightness of 500 lx, excite for 15 seconds, wait for 2 seconds before starting measurement, and the measurement time is 6 minutes.
[0071] (2) Hydrophobicity test: The test is carried out according to DL / T 627-2018 "Room temperature curing silicone rubber anti-pollution flashover coating for insulators".
[0072] After the samples were prepared and after the aging process, brightness test and water repellency test were performed to obtain brightness data group 1 and brightness data group 2, respectively. After the samples were prepared and after the aging process, respectively.
[0073] Data Analysis:
[0074] (1) The following formula is used to fit the data of brightness data group 1, and I is obtained: 0 and τ:
[0075]
[0076] Where, I is the luminescence intensity after the excitation stops at t; I 0 is the luminescence intensity when the excitation just stops; τ is the average lifetime of the electron in the excited state, which is also called the decay constant; K is a constant.
[0077] (2) Use the τ obtained in step (1) and the following formula to fit the data of brightness data set 2 to obtain I 1 :
[0078]
[0079] (3) The degree of aging of silicone rubber is defined as:
[0080]
[0081] The specific values of each parameter are shown in Table 1.
[0082] Example 2
[0083] Sample preparation:
[0084] (1) 100 kg of hydroxyl-terminated polydimethylsiloxane with a viscosity of 5000 mPa.s, 0.5 kg of hydroxyl silicone oil, and 10 kg of hydrophobically modified nano-silica were placed in a vacuum kneader and kneaded at 120-140°C and -0.1 MPa. After stirring and kneading evenly, 2 kg of Sr was added. 4 Al 14 O 25 :Eu 2+ ,Dy3+ , 90kg aluminum hydroxide, 20kg silicon oxide, fully knead and evenly mix, and use a three-roll mill for 3 times to further disperse evenly until it becomes a particle-free viscous liquid;
[0085] (2) adding the uniformly kneaded rubber material into a planetary disperser, adding 200 kg of solvent gasoline, 2 kg of vinyl trimethoxysilane, 2 kg of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 5 kg of methyl tributylidene oxime silane, and 0.3 kg of dibutyltin diacetate, and uniformly dispersing at a stirring speed of 2000 rpm, vacuum degassing, and discharging and canning to obtain a uniform mixture;
[0086] (3) The mixture obtained in step (2) is coated on a glass sheet to prepare a sample of 1.5 cm×1.5 cm×0.3 mm for later use.
[0087] The aging process, performance testing and data analysis were carried out according to the steps in Example 1.
[0088] Example 3
[0089] Sample preparation:
[0090] (1) 50 kg of hydroxyl-terminated polydimethylsiloxane with a viscosity of 1000 mPa.s, 50 kg of vinyl-terminated polydimethylsiloxane with a viscosity of 5000 mPa.s, 2 kg of hexamethyldisilazane, 0.6 kg of γ-glycidyloxypropyltrimethoxysilane, 100 kg of aluminum hydroxide, and 10 kg of hydrophobically modified nano-silica were placed in a vacuum kneader and kneaded at 120-160° C. and -0.1 MPa. After stirring and kneading evenly, 5 kg of Ca 2 MgSi 2 O 7 :Eu 2+ ,Dy 3+ , 20kg silicon oxide, fully kneaded and processed three times using a three-roll mill to further disperse evenly until it becomes a particle-free viscous liquid;
[0091] (2) adding the uniformly kneaded rubber material into a planetary disperser, adding 200 kg of solvent gasoline, 2 kg of hydrogenated silicone oil, 0.1 kg of 1-ethynylcyclohexanol, and 0.3 kg of Custer catalyst, and uniformly dispersing at a stirring speed of 2000 rpm, vacuum degassing, and discharging and canning to obtain a uniform mixture;
[0092] (3) The mixture obtained in step (2) is coated on a glass sheet to prepare a sample of 1.5 cm×1.5 cm×0.3 mm for later use.
[0093] The aging process, performance testing and data analysis were carried out according to the steps in Example 1.
[0094] Example 4
[0095] Sample preparation:
[0096] (1) 100 kg of methyl vinyl silicone rubber, 6 kg of hydroxy silicone oil, 0.2 kg of γ-glycidyloxypropyl trimethoxysilane, 20 kg of hydrophobically modified fumed silica, and 100 kg of aluminum hydroxide were placed in a vacuum kneader and kneaded at 120-160°C and -0.1 MPa. After stirring and kneading evenly, 7 kg of Sr was added. 3 MgSi 2 O 8 :Eu 2+ ,Dy 3+ , fully knead and process it three times using a three-roll mill to further disperse it evenly until it becomes a viscous liquid without particles;
[0097] (2) Add the above-mentioned uniformly kneaded rubber material into a planetary disperser, add 200 kg of solvent gasoline and 0.1 kg of vulcanizing agent dichloromethane, and disperse evenly at a stirring speed of 2000 rpm. After vacuum degassing, discharge the material and can it to obtain a uniform mixture;
[0098] (3) The mixture obtained in step (2) is coated on a glass sheet to prepare a sample of 1.5 cm×1.5 cm×0.3 mm for later use.
[0099] The aging process, performance testing and data analysis were carried out according to the steps in Example 1.
[0100] from Figure 2 It can be seen from the scattered points that the brightness decay rate of the sample before aging is similar to the brightness decay rate after 5 accelerated aging cycles, because after 5 accelerated aging cycles, the aging degree of the sample (Table 1) is not high, and the change of its surface hydrophobicity is not obvious; the brightness decay rate after further 10 accelerated aging cycles is significantly slowed down, because the hydrophobicity of the sample is reduced after accelerated aging (Table 2), causing some of the photoluminescent materials to fail due to the influence of moisture, and the overall initial brightness decreases. Therefore, within the same decay time (the decay time of the photoluminescent material not affected by moisture remains unchanged), the brightness decay rate is significantly reduced; the brightness decay rate after 15, 20, and 30 accelerated aging cycles is further slowed down.
[0101] from Figure 2 It can be seen from the fitting curve that the formula can fit the experimental data well, and the corresponding I 0 The corresponding aging degree evaluation is listed in Table 1. It can be seen that the aging degree of the sample is quantified and can well show the aging status and trend.
[0102] According to DL / T 627-2018 "Room-temperature curing silicone rubber anti-pollution flashover coating for insulators", the hydrophobicity test is carried out. Figure 3-Figure 7 The test results of the hydrophobicity of the sample surface before aging and after different accelerated aging cycles are shown respectively. It can be seen that with the increase of the number of accelerated aging cycles, the hydrophobicity level of the sample surface is constantly decreasing, but the water spraying method is essentially a qualitative description, and as shown in Table 2, even after experiencing different aging cycles, the sample is still at the same hydrophobicity level, and the method of the present invention can quantitatively and more accurately describe the aging degree of the sample.
[0103] Table 1 Fitting values of brightness and aging degree of samples in Example 1 after different aging cycles
[0104]
[0105]
[0106] Table 2 Hydrophobicity classification of samples in Example 1 after different aging cycles
[0107] sample Hydrophobicity classification After 0 accelerated aging cycles HC1 After 5 accelerated aging cycles HC1 After 10 accelerated aging cycles HC2 After 20 accelerated aging cycles HC3 After 30 accelerated aging cycles HC3
[0108] In summary, the method of the present invention can clearly and obviously quantitatively evaluate the aging degree of the silicone rubber material.
Claims
1. A method for evaluating the aging degree of silicone rubber, characterized in that: The steps include: (1) spraying / coating a silicone rubber composition containing a photoluminescent material on an object to be coated; (2) after the silicone rubber composition is cured, using a laser emitter to emit excitation light to the silicone rubber composition to excite the silicone rubber composition; (3) using a light intensity tester to measure the emission intensity of the silicone rubber composition excited in step (2), and recording the change of the light intensity of the silicone rubber composition over time as data set 1; (4) After the coating material is aged, a laser emitter is used to emit excitation light to the silicone rubber composition at the location where the silicone rubber aging degree is to be detected, thereby exciting the silicone rubber composition; (5) using a light intensity tester to measure the emission intensity of the silicone rubber composition excited in step (4), and recording the change of the light intensity of the silicone rubber composition over time as data set 2; (6) analyzing the light intensity versus time curve recorded in step (5) to evaluate the aging degree of the silicone rubber composition; The measurement of the change in light intensity of the silicone rubber composition over time in step (3) and step (5) should be carried out at the same time as the excitation of the silicone rubber composition in step (2) and step (4) is completed respectively; (7) Data analysis: (71) The following formulas are used to fit the data of data set 1 to obtain I0 and τ: Where I is the luminous intensity t hours after the excitation stops; I0 is the luminous intensity when the excitation just stops; τ is the average lifetime of the electron in the excited state, which is also called the decay constant; K is a constant; (72) The data of data set 2 are fitted using τ obtained in step (71) and the following formula to obtain I1: (73) The degree of aging of silicone rubber is defined as: The silicone rubber composition contains the following raw materials in percentage by mass:
2. The method for evaluating the aging degree of silicone rubber according to claim 1, characterized in that: The amount of data collected about the emission intensity of the silicone rubber composition excited in step (3) is 10-100.
3. The method for evaluating the aging degree of silicone rubber according to claim 1, characterized in that: In step (2), the laser emitter irradiates the in-service silicone rubber composition to be inspected for an irradiation time of 10s-20min.
4. The method for evaluating the aging degree of silicone rubber according to claim 1, characterized in that: The measurement time of the emission intensity of the silicone rubber composition excited in step (2) is 1s-400s.
5. The method for evaluating the aging degree of silicone rubber according to claim 1, characterized in that: The wavelength of the excitation light provided by the laser emitter in step (2) depends on the photoluminescent material to be excited, and the wavelength range of the excitation light is 200nm-1500nm.
6. The method for evaluating the aging degree of silicone rubber according to claim 1, characterized in that: The mass fraction of the photoluminescent material particles is 1%-10%.
7. The method for evaluating the aging degree of silicone rubber according to claim 1, characterized in that: The photoluminescent material is selected from one or more of aluminates, silicates, phosphates, borates, sulfides, sulfur oxides, and nitrides.
Citation Information
Patent Citations
Resin deterioration evaluation test method and resin recycling method
EP3725832A1